Site-specific patterns of fine root biomass formation across European coniferous forests - Yury Karpechko; Anna Karpechko; Andrej Tuyunen (Forest Ecosystems, 2025)
Fine roots play a crucial role in the biogeochemical cycles of terrestrial ecosystems. Patterns of fine roots biomass formation for broad geographical areas are still unclear. We use published estimates of characteristics of European pine and spruce stands to determine their productivity and calculate the needle biomass. Then, the relationship between the fine-root:needle biomass ratio of European pine and spruce forests and the stand quality index, which is a proxy of soil fertility, was determined. We show that a rise in soil fertility is accompanied by a decrease in this ratio. Moving from the northern edge of the boreal zone southwards, with the related rise in air and soil temperatures, we see a decline in the mass ratio of fine roots and needle. The change in the fine-root:needle biomass ratio is controlled by the change in specific water uptake by roots, which is related to the osmotic pressure of the solution in the absorbing root's central vascular cylinder. The fine-root:needle ratio does not vary among stands of the same age if the stand quality index and the geographical latitude (a proxy of air and soil temperatures) are constant. These findings may be useful for further in-depth analysis of forest ecosystem functioning in Europe.